Professor of mathematics Aronas Naftalevičius (1921–1999) (a survey of the life and activity in Vilnius University - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2011)
A. Naftalevičius life review. Scientific work. Bibliographical listing.